PTU-106 Identifying true immune-tolerant disease in children and young adults with chb using quantified hepatitis b surface antigen levels. (22nd June 2015) - Hansi, N; Gill, US; Banerjee, M; Naik, S; Tong, W; Foster, GR; Carey, I; Kennedy, PT
Abstract : Introduction: Immune tolerant (IT) chronic hepatitis B (CHB) is a clinical definition based on normal serum ALT and high HBV DNA. NICE guidelines identify a need to improve knowledge of the natural history of eAg+ IT disease. Importantly, recent studies have reported an inverse relationship between quantitative HBsAg (qHBsAg) and the degree of liver fibrosis in eAg+ patients. 1 We aimed to explore the utility of qHBsAg in combination with clinical variables to more accurately define the IT disease phase in young patients. Method: Children and young adults were followed in dedicated clinics. 155 consecutive treatment naïve, eAg+ patients were included for analysis; female = 79, median age 22 (range 6–30). Data on longitudinal ALT, HBV DNA and Ishak fibrosis stage (FS) were recorded. HBsAg levels were quantified to elucidate its relationship with IT disease. Results: There was no correlation between qHBsAg and age, HBV genotype or ALT levels (p = ns). High HBV DNA correlated with high qHBsAg; HBV DNA >8 log, (p = 0.016); HBV DNA >9 log (p = <0.001). 133/155 patients underwent liver biopsy. Patients with FS 0–2, indicating no or minimal liver damage, demonstrated higher qHBsAg compared to patients with a higher FS (≥3) p = 0.01. Combining clinical parameters (ALT <40, HBV DNA >8 log, FS 0–2), to denote the IT disease phase; we noted significantly higher qHBsAg levels in IT vs. non-IT eAg+ patients (p = <0.001). Mean qHBsAg was 139, 471 IU/ml (5.14 log) in patients considered IT. Interestingly, qHBsAg >1, 000, 000 IU/ml (6 log) was only seen in patients who had the combined clinical parameters of ALT, HBV DNA and FS consistent with IT disease; thus representing a theoretical qHBsAg threshold to identify genuine IT patients. Conclusion: Serum ALT and HBV DNA alone do not accurately define IT CHB. We demonstrate that high qHBsAg levels combined with these parameters can more accurately characterise IT disease, confirmed histologically with minimal or no fibrosis. We propose that qHBsAg used in combination with serum ALT and HBV DNA could obviate the need for liver biopsy in young patients. Disclosure of interest: None Declared. Reference: Marcellin P, Martinot-Peignoux M, Asselah T, et al . Serum levels of hepatitis B surface antigen predict severity of fibrosis in patients with E antigen-positive chronic hepatitis B. Clin Gastroenterol Hepatol. 2014